2012
DOI: 10.1016/j.jval.2012.08.2017
|View full text |Cite
|
Sign up to set email alerts
|

PRS18 Systematic Review of Economic Evaluations, Utility Estimates, Resource Utilisation, and Costs in Chronic Idiopathic Urticaria

Abstract: Compared to symptomatic therapy, patient with AR treated with allergen immunotherapy obtained approx. 0.75 month (3 years of vaccination followed by 5-year evaluation) and 3.45 month (4-year follow up including 3 years of vaccination) without AB. The QALY for costs has been calculated between 8516 €-8883 €. CONCLUSIONS: In the Slovak Republic, Staloral allergen immunotherapy of allergic rhinitis is effective from the clinical as well as pharmacoeconomic point of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although this review included a large number of cost studies by proportion, previously conducted reviews primarily considered economic evaluations such as CEAs and CUAs and therefore reported a high proportion of CEAs and CUAs and studies involving model-based analyses [ 29 , 30 , 38 – 40 ]. For those reviews, 62% to 100% of studies included were CEAs or CUAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this review included a large number of cost studies by proportion, previously conducted reviews primarily considered economic evaluations such as CEAs and CUAs and therefore reported a high proportion of CEAs and CUAs and studies involving model-based analyses [ 29 , 30 , 38 – 40 ]. For those reviews, 62% to 100% of studies included were CEAs or CUAs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a database search, references cited in each of the included studies and relevant (but not included) systematic reviews were manually searched to identify any additional relevant studies, as recommended by the CRD and Cochrane guidelines [ 29 , 30 ]. A hand search of select academic, industry, and medical society proceedings from 2018 to 2020 was also conducted to identify any recent publications that may not have been published yet, including those from the International Society for Pharmacoeconomics and Outcomes Research (ISPOR), the European Association of Hospital Pharmacists, and the Society for Investigative Dermatology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation